The Effects of Agility Exercise and Eye-Foot Coordination against The Dribbling Capability Football Training Players Bintang Pelajar (Journal of Physical Education and Sports, 2018)
The purpose of this study is to know and analyze the effect of agility training and eye-foot coordination (experimental study of T-Drill training and 40 Yard Ladder Sprint on the football star student training players in Semarang in 2018. This research method is an experimen twith a 2x2 factorial design. Data analysis technique using Analysis of Varian (ANOVA) ats ignificance level (Î±) 0.05 Independent variable in this research that is T-Drill and 40 Yard Ladder Sprint Training of high and low eye-foot coordination as attribute variable and dependent variable the dribbling skills. The population in this study is Football Training Players Bintang Pelajar of Semarang district in 2018 which amounted to 60. The sampling technique using purposive sampling with then umber of samplesof 40 players. There sults of this study: There is a significant influence difference between T-Drill and 40 Yard Ladder Sprint against dribbling ability with sig value (0.004) < Î±(0.05) and Fvalue (9.758) > Ftable (5.117), There is influence between high and loweye-foot coordination with damping ability where significan cevalue (0.010), < Î±(0.05) and Fvalue (7.374) > Ftable (5.117). There is no significant interaction between agility training and eye foot coordination on dribbling ability with sig value (0.231) > Î±(0.05) and Fvalue (1.487 ) < Ftable (5.117).